2018
DOI: 10.1002/jbm4.10087
|View full text |Cite
|
Sign up to set email alerts
|

Static Preload Inhibits Loading‐Induced Bone Formation

Abstract: Nearly all exogenous loading models of bone adaptation apply dynamic loading superimposed upon a time invariant static preload (SPL) in order to ensure stable, reproducible loading of bone. Given that SPL may alter aspects of bone mechanotransduction (eg, interstitial fluid flow), we hypothesized that SPL inhibits bone formation induced by dynamic loading. As a first test of this hypothesis, we utilized a newly developed device that enables stable dynamic loading of the murine tibia with SPLs ≥ −0.01 N. We sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…The effect of altering this initial (or resting) load level itself, or in combination with other loading parameters has not been systematically examined in the axial tibial loading model. A recent study using a novel off‐axis compression tibial loading model in 4‐month‐old female BALB/c mice showed that even when keeping the change from pre‐load to peak load similar (−3.8 N), increasing the static pre‐load from −0.03 to −1.5 N had detrimental effects on bone formation, even though the greatest pre‐load (−1.5 N) also corresponded to the greatest applied peak load (−5.3 N) . These results may depend upon the genetic strain, age of mouse, and loading protocol employed, but suggest that choice of pre‐load magnitude can have important effects upon the load‐induced anabolic response of both cortical and cancellous bone tissue.…”
Section: Experimental Parameters To Consider For In Vivo Loading Expementioning
confidence: 99%
“…The effect of altering this initial (or resting) load level itself, or in combination with other loading parameters has not been systematically examined in the axial tibial loading model. A recent study using a novel off‐axis compression tibial loading model in 4‐month‐old female BALB/c mice showed that even when keeping the change from pre‐load to peak load similar (−3.8 N), increasing the static pre‐load from −0.03 to −1.5 N had detrimental effects on bone formation, even though the greatest pre‐load (−1.5 N) also corresponded to the greatest applied peak load (−5.3 N) . These results may depend upon the genetic strain, age of mouse, and loading protocol employed, but suggest that choice of pre‐load magnitude can have important effects upon the load‐induced anabolic response of both cortical and cancellous bone tissue.…”
Section: Experimental Parameters To Consider For In Vivo Loading Expementioning
confidence: 99%
“…z = 50 % cross sections of the mouse tibia, two commonly investigated sections within the limb (Srinivasan et al. 2019 ; DeLong et al. 2020 ; Rooney et al.…”
Section: Methodsmentioning
confidence: 99%
“…This strain threshold was, however, found to vary with loading conditions, locations, loading waveform, frequency of loading etc. [4]–[10]. For example, the strain thresholds reported for the cantilever loading of mouse tibia, with trapezoidal loading waveform are about 650 με [4] and 850 με [5], with and without rest-inserted waveform, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…For axial loading of tibia, the strain threshold was found to be approximately 1100 με [9]. Bone formation rate (BFR) was further found to depend on axial preloads, with higher BFR for lower axial preload, possibly due to preload-dependent strain threshold [10].…”
Section: Introductionmentioning
confidence: 99%